The Language of Dance (Wesleyan University Press, 1974)
Mary Wigman was one of the most celebrated dancer/choreographers of the modern era, and was an iconic figure in Weimar German culture. She was known for her incorporation of non-Western instrumentation and dance, as well as for pioneering work in dance therapy. In addition to documenting important cultural history, this autobiography demonstrates Wigman's personal passion and her role in shaping the art form.